STRUCTURALISM OF CHARACTER VALUES IN THE NOVEL â€œONE YEAR ACADEMICâ€ BY JUNIOR DANY WIBISONO - Syaiful Bahri (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2023)
This study aims to determine the value theory of character education and structural theory. In line with the research objectives, this research uses qualitative research using descriptive methods. The data used in this study is a combination of intrinsic and extrinsic elements of literary works which include structural theory and the values of character education contained in the novel. The data source used in this research is the novel "One Academic Year" by Junior Dany Wibisono. The results of the analysis of the One Academic Year novel include structural theories such as intrinsic elements consisting of: (1) theme, namely the intrinsic elements of the novel which are the basis of the story, (2) plot/plot which is the storyline, (3) setting which refers to the background. time, atmosphere, and place of the story, (4) characterization is the determination of the character or character of the character, (5) point of view, namely the direction of a writer's point of view in conveying a story, (6) mandate, which is a moral message written by the author of the story. In addition, there are also extrinsic elements. The extrinsic element is the opposite of the novel's intrinsic element. The extrinsic elements of the novel are elements that are outside the literary work, but indirectly affect the structure of the literary work. The extrinsic element of a literary work depends on the author telling the work. Extrinsic elements for example are the values contained, background, and social situation. After structural theory, there are also character education values contained in the novel.